Changes in the food and drink consumption patterns of Australian women during the COVID‐19 pandemic. (1st September 2022) - Tolhurst, Tara; Princehorn, Emily; Loxton, Deb; Mishra, Gita; Mate, Karen; Byles, Julie
Abstract: Objective : This paper uses data from the seventh fortnightly Coronavirus (COVID‐19) Survey sent to women in the Australian Longitudinal Study on Women's Health to investigate the relationship between the COVID‐19 pandemic and the food and drink consumption of women born in 1946‐51, 1973‐78 and 1989‐95. Methods : A survey about changes in fruit, vegetable, discretionary food, takeaway and sugary drink consumption during the pandemic was emailed on 22 July 2020 to 28, 709 women in three cohorts of the Australian Longitudinal Study on Women's Health. Thematic qualitative analysis was conducted on comments about changes in consumption, and basic quantitative analysis was included for context. Results : There were significant associations between age and all categories of food and drink consumption. Women wrote of lifestyle changes and choices during lockdowns, comfort and emotional eating, and access to food and drink changing their consumption behaviours. Conclusions : The COVID‐19 pandemic and interventions had both positive and negative impacts on the food and drink consumption behaviours of Australian women. Implications for public health : These findings can be used to directly influence practice around healthy food and drink consumption, highlighting enablers, including being at home, and barriers, including mental health, that should be considered.